Makna Tahun Represi Digital Dalam Cover Koran Tempo Edisi 21 Oktober 2020 - Yudi Sudiana; Alfian Muhazir (AGUNA: Jurnal Ilmu Komunikasi, 2021)
Freedom of expression often does not go hand in hand with rulers. This is what the October 21, 2020 edition of Koran Tempo wants to depict, entitled “The Year of Digital Repression”. Through this research, the writer wants to examine further the meaning of the year of digital repression in the cover of Koran Tempo through Peirce's semiotic analysis. The results of this study show that Koran Tempo's cover packs the meaning of the digital year of repression through two types of visual elements, namely typography, in the form of writing in the form of sentences and human illustrations that are identical to the visualization of the police, the man disguised as a meatball seller, the hooded man holding the hashtag. and someone running. Both symbols are packaged in detail so that they can give a strong message meaning. The existence of the visualization of the police is depicted as a representative of the authorities who are given the impression of being the party carrying out repression. The hooded man implies the existence of an anonymity account that is described as a buzzer in digital media. This figure plays an important role in building hashtags with potential trending topics. Meanwhile, the meatball vendor holding the handie talkie implies an extension of the police. On the other hand, the typographic elements in the cover contain message content that supports the illustration image. In short, all of these elements lead to the meaning that the swift criticism of the government in the digital realm has prompted increasingly stringent regulations.Keywords: Cover, Digital, Tempo Newspaper, Repression, Semiotics